THE RIGHT TO DEMOCRACY ARRANGEMENT UNDER INTERNATIONAL LAW - Rika Kurniaty (Trunojoyo Madura University, 2019)
In the historical context, during the Cold War, due to the tension of ideology between countries, the link between international law and the notion of democracy only received few discussions and interest by international law scholars. The fall of communism in the early 1990s has put liberal democracy - as the only legal system of government - back on the global agenda. The victory of democracy throughout the world quickly led to the claim that there is now a right to democracy in international legal instruments and the existence of democracy as a guiding principle in general international law. However, the word